ADIKSI INTERNET PADA PERILAKU FEAR OF MISSING OUT (FOMO): Studi Fenomenologi Pada Komunitas Penggemar BTS (ARMY) Di Media Sosial - Haniifah Zahra (2024)
The development of technology and the internet has made social media an integral part of individuals' lives. Intensive use, especially with high intensity, triggers addiction behavior. This social media addiction then contributes to the emergence of feelings of excessive fear of missing out on information or what can be said as Fear of Missing Out (FoMO). The author in this study focuses on the phenomenon of Fear of Missing Out in the BTS fan community (ARMY) to see how social media addiction can affect FoMO and understand the process of FoMO itself in the fan community. This research uses hermeneutic phenomenology method and qualitative approach. The results show that the high intensity of social media use triggers social media addiction which has an impact on Fear of Missing Out (FoMO). The results of this study also show that there are two processes of Fear of Missing Out (FoMO), namely the perception of missing out manifested by fear of loss and compulsive behavior as an effort to reduce feelings of Fear of Missing Out.